USING STEALTH TECHNOLOGIES IN MOBILE ROBOTIC COMPLEXES AND METHODS OF DETECTION OF LOW-SIGHTED OBJECTS - Rudyk, Andrii; Semenov, Andriy; Semenova, Olena; Kakovkin, Sergey (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2021)
The paper outlines the latest technologies used by the world’s leading manufacturers in the development of mobile low-observable robotic systems and promising measures to improve the quality of components and design of such objects. Methods of detecting objects using stealth technologies are considered, and it is shown that only due to a system approach it is possible to compensate for the reduction of the effective scattering surface of low-observable objects by technical means of radar stations. It is shown that the main method of increasing the range to the radio horizont is the use of an air-based radar. Methods of detecting objects on the traces of their interaction with the environment are promising for organization of cooperation of several radars in the detection of low-observable objects.